A Syndrome of Variable Allergy, Short Stature, and Fatty Liver - Qiao, Jing; Chen, Yue; Lu, Ying; Wang, Tiejun; Li, Xiaoli; Qin, Wei; Li, Aifen; Chen, Guangquan (Frontiers in Genetics, 2022)
SLC22A18 (solute carrier family 22 member 18) is an imprinted gene, but its role in growth and development is not clear. In the present study, we recorded the clinical information of six male patients of six unrelated families. Real-time quantitative PCR, Sanger sequencing, and DNA methylation sequencing were performed in these patients. The results suggested that the patients with the clinical characteristics of allergic allergy, short stature, and fatty liver had a lower expression of SLC22A18. One novel variant (chr11: 2899732 delA) with clinical significance was found in the core promoter region of the patients. Overall, this study found a syndrome associated with SLC22A18.